2019
DOI: 10.1515/npf-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Putting Humpty Together Again: How Reputation Regulation Fails the Charitable Sector

Abstract: Investigations of how Oxfam Great Britain (GB) managed its safeguarding systems and handled revelations of sexual exploitation by its staff highlighted a variety of internal governance and culture issues, and a lack of transparency as it sought to protect its reputation. The current models of reputation management do not fully explain its actions, however. This article argues that five systemic factors in the environment in which nonprofits operate create undue pressures for protection of reputations and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The new Italian legislation accommodates the idea of self-regulation, emphasising the key role that CSOs networks can now play in self-monitoring the sector. On the contrary, self-regulation has been heavily criticised in the aftermath of charity scandals that took place elsewhere in the world, especially in the case of Oxfam GB in Haiti 2018, in which self-regulation was labelled as ill-suited in providing adequate oversight of what emerged as the central problem in the Oxfam case (Phillips, 2019). In its report on the sexual exploitation and abuse in the British aid sector, The House of Commons International Development Committee concluded that the sector and the legislator should move beyond self-regulation, because it failed to ensure that safeguarding standards are being upheld by CSOs (House of Commons International Development Committee, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The new Italian legislation accommodates the idea of self-regulation, emphasising the key role that CSOs networks can now play in self-monitoring the sector. On the contrary, self-regulation has been heavily criticised in the aftermath of charity scandals that took place elsewhere in the world, especially in the case of Oxfam GB in Haiti 2018, in which self-regulation was labelled as ill-suited in providing adequate oversight of what emerged as the central problem in the Oxfam case (Phillips, 2019). In its report on the sexual exploitation and abuse in the British aid sector, The House of Commons International Development Committee concluded that the sector and the legislator should move beyond self-regulation, because it failed to ensure that safeguarding standards are being upheld by CSOs (House of Commons International Development Committee, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, this finding may raise the general question of how the UNGC framework needs to be improved to strengthen NPOs' incentives to continuously engage in local networks. Critical voices have argued that NPOs can be found to join social responsibility initiatives for reputational purposes while neglecting the actual implementation of their regulation standards [24,35]. A better understanding of how the initiative needs to be improved to incentivize continued engagement of NPO is therefore required.…”
Section: Discussionmentioning
confidence: 99%
“…One may also address NPOs' motivation to engage in such an initiative. Critics argue that, similar to their business counterparts, NPOs are also prone to joining social responsibility initiatives for reputational purposes while lacking commitment over time [24,35]. Subsequently, in light of the important role of NPOs within the UNGC framework, but even more so to address the criticisms mentioned above, research has yet to assess the extent to which NPOs effectively strengthen the UNGC.…”
Section: The United Nations Global Compact: Introducing Npos' Perspectivementioning
confidence: 99%
“…In response to the power imbalance of the aid system, a recipient-centered aid system requires diverse and inclusive aid staff that can minimize gender discrimination and thus reduce sexual abuse. International development scholars have demonstrated that "a critical mass of racial/ethnic diversity improves performance" and "genuine inclusiveness creates greater opportunities to motivate change" (Phillips, 2019). But aid organizations currently lag behind on promoting diversity and inclusiveness.…”
Section: Path To Accountability: Civil and Administrative Remediesmentioning
confidence: 99%
“…But aid organizations currently lag behind on promoting diversity and inclusiveness. Of the leading 500 aid organizations in the UK, two-thirds of the trustees are male and more than half of the boards are all White (Phillips, 2019). Lack of diversity and inclusiveness weakens the effectiveness of governance and aid delivery.…”
Section: Path To Accountability: Civil and Administrative Remediesmentioning
confidence: 99%